2017
DOI: 10.1016/j.trd.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A multiple ship routing and speed optimization problem under time, cost and environmental objectives

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…As stated earlier, the sailing speed is a key decision variable in the expressions of fuel consumption, SO x emissions, and delivery delay. Many scholars have examined the sailing speed and its impacts on various factors, including but not limited to Wang et al [17], Wen et al [18]. More recently, Psara is and Kontovas [8] summed up the existing sailing speed optimization models, most of which take the sailing speed as an input to the decision-making problem [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…As stated earlier, the sailing speed is a key decision variable in the expressions of fuel consumption, SO x emissions, and delivery delay. Many scholars have examined the sailing speed and its impacts on various factors, including but not limited to Wang et al [17], Wen et al [18]. More recently, Psara is and Kontovas [8] summed up the existing sailing speed optimization models, most of which take the sailing speed as an input to the decision-making problem [19,20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was anticipated that as a consequence of SECA regulations, ship operators may reduce the sailing speed to compensate for the extensive cost caused by SECA compliance as noted by Zis and Psaraftis [16]. In order to analyze the impact of slow steaming on the carrier's and the shipper's costs, Mallidis, et al [30] developed continuous-time analytical models. Further, Wen, et al [31] presented a speed optimization algorithm that can be applied by shipowners to optimize the vessel´s fuel consumption.…”
Section: Slow Steamingmentioning
confidence: 99%
“…In order to analyze the impact of slow steaming on the carrier's and the shipper's costs, Mallidis, et al [29] developed continuous-time analytical models. Further, Wen, et al [30] presented a speed optimization algorithm that can be applied by shipowners to optimize the vessel's fuel consumption. Studies by Johnson and Styhre [31] and Zis and Psaraftis [16] suggested that reduced waiting time in port could support slow steaming and mitigate the additional cost effects of SECA for dry bulk shipping in the North and Baltic Seas.…”
Section: Slow Steamingmentioning
confidence: 99%
“…Kim, et al [37] set carbon taxation as a constraint of the fuel-cost minimization model. Wen, et al [38] proposed a cost minimizing model and an alternative, single-objective optimization model, including minimizing trip duration and minimizing emissions.…”
Section: Sustainable Operation Objectivesmentioning
confidence: 99%